PENGEMBANGAN SISTEM ADMINISTRASI PEMBAYARAN SUMBANGAN PEMBINAAN PENDIDIKAN (SPP) SEKOLAH MENENGAH ATAS BERBASIS WEB - Ridho Ronaldi Eka Putra; Dwi Sakethi (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2021)
School is a level and continuous education unit for organizing teaching and learning activities. The system of financial administration of students at schools such as SPP (tuition) payments is one example of administration system that most of the data writing still use manual system. Writing data using a manual system sometimes has errors (human error) and data loss, this is because the writing and storage is done as well and less precision when entering data. Developing a Web-based school's financial administration information system using the Laravel Framework resolves these issues. In this study, system development used the PHP programming language and the Laravel Framework. Functional testing System using Black Box testing with Equivalence Partitioning (EP) method. The result of the developed system provides the school's ease of logging the student SPP (tuition) payment.